Cysticercosis of the nervous system: less frequent clinical forms III- spinal cord forms - Horacio M. Canelas; Oswaldo Ricciard-Cruz; Ovidio A. D. Escalante (Arquivos de Neuro-Psiquiatria)
The spinal forms of cysticercosis are rather rare (2.7% of 296 cases of neurocysticercosis recorded in the Department of Neurology of the University of São Paulo Medical School). In a survey of the literature only 42 cases were found, most of them associated with cerebral symptoms. The reasons for this low incidence, as well as the possible routes followed by the parasite in its approach to the spinal cord, are discussed. After a review of the first cases reported in the literature, the authors refer the main syndromes (meningomyelitides, tabetiform pictures and spinal cord compressions) and some of the clinico-pathologic features of spinal cysticercosis. Nine cases of spinal cysticercosis are reported. The diagnosis was based on laboratorial data (mainly the complement fixation test for cysticercosis in the cerebrospinal fluid) or in the results of surgical therapy. Other cerebrospinal fluid findings (presence of eosinophile cells, protein contents, and the results of the manometric tests) are discussed. Myelographic block was demonstrated in 5 cases. Three of these patients were submitted to laminectomy, with variable results. The prevailing neurological picture was that of spinal cord and/or root compression (4 cases). Two patients showed a dorsal funiculi syndrome closely simulating tabes dorsalis. Two other patients presented a picture of meningomyelitis with no systematization. One patient had a syndrome suggestive of subacute combined degeneration of the spinal cord, but the presence of cerebral symptoms and the laboratorial data pointed to cysti-cercosis as the main disease process.